The films of Jocelyne Saab : films, artworks and cultural events for the Arab world - Rouxel, Mathilde; Van de Peer, Stefanie (ReFocus: the international directors series., 2021)
Jocelyne Saab was one of the most important female filmmakers pioneering a sense of international emancipatory world cinema from the early 1970s to her death in 2019. This study is dedicated to her entire oeuvre which consisted of journalism, documentaries, experimental and feature films, as well as photography, art exhibitions and curation, and film festival organisation. A range of international scholars integrates her work into a cohesive study of all aspects of her oeuvre - filmic, activist and artistic - representing the global significance of Saab's work and the ongoing resonance of her ideals and activism in a worldwide perspective.